Harshness and unpredictability during childhood: an approach from life-history theory to understanding risk behaviors - Guzmán-Lavín, Eugenio J.; Figueroa, Oriana; Muñoz-Reyes, José Antonio; Aldunate, Nerea; Polo, Pablo (Frontiers in Psychology, 2025)
IntroductionPrevious studies have investigated the relationship between childhood experiences of harshness and unpredictability and risky adult behaviors from a life-history theory perspective. However, findings have been inconsistent, suggesting that the relationship between early environments and current behavior is complex and may be influenced by moderating variables. This study examined whether childhood harshness (resource scarcity) and unpredictability (proximal environmental instability) were positively related to risk propensity, considering reproductive strategy-related trade-offs (i.e., the age of first sexual intercourse and the age of menarche) and current environmental factors (i.e., being in a committed relationship, perceived family support, and poverty rate of the participant's municipality) as potential moderators.MethodsWe sampled 368 individuals in two settings: college classrooms and a controlled laboratory environment.ResultsOverall, we did not find a clear relationship between perceived childhood environment and risk-taking. Contrary to expectations, we found a positive relationship between perceived childhood harshness and risk propensity in women who delayed their first sexual intercourse. Exploratory analyses by data collection setting revealed that harsh and unpredictable childhood environments may impact risk propensity differently, though no coherent pattern emerged.DiscussionThis study underscores the importance of context dependence and the need to consider additional variables that may moderate the relationship between childhood experiences and risk-taking behaviors.